Fetomaternal outcomes in patients undergoing cesarean after previous 1 or more cesarean section at Government Medical College, Saharanpur - Singh, Rashmi; Rehman, Aisha; Rabbani Ismaili, Owais Maqbool; Vishlux, Poolomsha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: There is an increase in trend of caesarean section in most countries worldwide, resulting in the rise of multiple repeat cesarean sections which is known to be associated with increase in maternal and perinatal morbidity and mortality rates. We decided to study the various fetomaternal outcomes in patients undergoing caesarean section at our institution. Methods: This prospective study was carried out in department of obstetrics and gynecology, Government Medical College, Saharanpur (UP) over a period of 14 months. All patients undergoing caesarean section for various indications at Government Medical College, Saharanpur with previous one or more caesarean section were included. History taking and examination was done. Maternal and fetal outcomes were noted. Results: Over a span of 14 months (September 2023 - December 2024), out of total 240 cesarean deliveries, 139 patients had at least 1 prior LSCS. Of these, 62.58% were emergency cases, and 37.43% were elective. 42.44% were aged 26-30 years, with only one patient over 40 years. 38.13% were gravida 2. Most common indication was short interpregnancy interval in 15.10%. Most frequent intra operative complication was adhesions in 31.65%. 8 cases with previous 1 LSCS needed NICU admission. Conclusions: With rise in repeat cesarean section there lies increase in maternal and fetal risks. Hospitals should conduct cesarean audits to reduce primary cesarean section rates, promote trial of labor after cesarean (TOLAC) for successful vaginal birth after cesarean (VBAC), and counsel patients on vaginal birth after cesarean (VBAC) risks and benefits to reduce repeat c-sections and complications.